Preclinical efficacy of a virus-like particle-based vaccine against avian influenza H5N1. (June 2009) - Arnon, Ruth; Ben-Yedidia, Tamar
Evaluation of: Kang S-M, Yoo D-G, Lipatov AS et al. : Induction of long-term protective immune responses by influenza H5N1 virus-like particles. PLoS ONE 4, e4667 (2009). This article describes a long-term protective effect of a vaccine candidate against avian influenza H5N1 that is based on A/Viet Nam1203/04 proteins within nonreplicating virus-like particles. The protective effect is correlated with both humoral and cellular immune responses.